A Systemic Disquisition on Pancreatic Neoplasia in all age groups: An Exhaustive Appraisal of Diagnostic Stratification, Histopathological Paradigms, and the Multimodal Oncotherapeutic Spectrum based on 13 high end studies - Sarkar, Suhena; Biswas, Birupaksha; Banerjee, Kaustuv; Bale, Jefri S.; Tamelan, Paul G. (Journal of Neonatal Surgery, 2025)
Pancreatic neoplasms represent one of the most insidious and biologically aggressive oncological entities, often eluding early detection and exhibiting dismal prognostication despite evolving molecular and therapeutic frontiers. This systematic review synthesizes evidence from 13 pivotal, high-impact studies to elucidate the diagnostic modalities, histopathological intricacies, and advanced oncologic treatment modalities—including chemotherapeutic regimens, molecular-targeted therapies, and surgical innovations—in pancreatic malignancies. Through comprehensive analysis, this review seeks to integrate clinical, histomolecular, and therapeutic determinants into a cohesive algorithm for contemporary management